“EMBRIÃO” de centro de parto normal fundamentado na experiência de formação de enfermeiros obstetras - Faria, Denise Gonzalez Stellutti de (2015)
Introduction: The obstetric care model in Brazil has been the subject of much discussion and research. Attention has centered on the need to consider women’s autonomy during the delivery process and the inclusion of midwives and obstetric nurses in the conduct of low-risk labor and birth. In-hospital normal birth centers (IHNBC) constitute an appropriate model for the care of women in labor and for the incorporation of practices recommended by the World Health Organization (WHO). Objective: To present a proposal of implementation and development of an IHNBC. Methods: This study is divided into chapters and includes a comprehensive review of the literature on the following topics: the Brazilian obstetric care process and the identification of ways to decrease the extremely high rates of cesarean sections in the country; Obstetric Violence; Childbirth Humanization; training and performance of midwives and obstetric nurses; and Normal Birth Centers and Birth Houses. This review supported the creation and implementation of the proposed IHNBC. The hospital that served as a research field is located in the state of São Paulo and offers obstetric care to women who use the Unified Health System (SUS). It also serves as a traineeship field for undergraduate medical and nursing students, medical residents and obstetric nursing specialization students. Results: We present environmental, social and programmatic characteristics (protocols) of the proposed IHNBC, according to the recommendations of the WHO and Ministry of Health. Additionally, we discuss the strengths, difficulties, expectations and perspectives of the development process, in order to comply with the “Stork Network” prerogatives (rede Cegonha, in Portuguese). Conclusion: In the specific context of this research, we expect that the proposed IHNBC implemented in the analyzed obstetric unit continues to be valued by managers and receives greater medical involvement. Moreover, we hope that this proposal is effectively implemented in the assessment phase according to the standards of the Stork Network, with the effective participation of midwives and obstetric nurses, and that this resut in the humanization of obstetric care, the assignment of greater value and recognitition to obstetric nursing and increased normal delivery rates.